ผลของสารสกัดเห็ดกระถินพิมาน Phellinus linteus ต่อความเป็นพิษของเซลล์และการแสดงออกของยีนในเซลล์มะเร็งปากมดลูก - ธนวิชญ์ แสงคีรีพัฒน์ (จุฬาลงกรณ์มหาวิทยาลัย, 2021)
Cervical cancer is one of cancer which has high incidence and mortality rate. Although, there is vaccination to prevent human papilloma virus infection, which is a major cause of cervical cancer, in some countries, especially lower and middle-income countries, they can’t access this vaccination. Nowadays, there are the new ways for healing and preventing tumorigenesis, especially the using of natural-product such as Phellinus linteus. The aim of this study is to study the antitumor ability of 3 extracts, Phellinus linteus extract, Mixture extracts (Mixture A and B) which contain Phellinus linteus and the other herbs as a component in cervical cancer cell lines. From the result, these 3 extracts can inhibit the cell viability level of C33a, SiHa and HeLa cell after 2 days of treatment, but there is high level of cytotoxicity in HEK293 cell. Moreover, Mixture B extract significantly decrease the level of cell proliferation of SiHa cell (p = 0.005), when compare with control group, resulting in significantly decreasing CDK7 and MKI67 gene expression. In the same way, the extract of Phellinus linteus significantly decrease the level of cell proliferation of C33a (p = 0.025), when compare with control group, and also leading to these two gene expression reductions significantly.